Peningkatan Kemampuan Mengenal Huruf Hijaiyyah Anak TK B Melalui Media Flashcard - Miranti, Miranti; Akbari, Akbari (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The ability to recognize Hijaiyyah letters is an essential skill that should be introduced in early childhood because it serves as the foundation for reading the Qur’an and supports the development of children’s religious and moral values. Early childhood is considered the golden period of development, making appropriate learning stimulation necessary to optimize all aspects of growth, including early religious literacy. However, observations at TK Negeri Pembina Pemulutan Barat showed that many children aged 5–6 years still had difficulty recognizing Hijaiyyah letters, particularly in distinguishing letters with similar shapes and sounds. These challenges were influenced by conventional teaching methods and the limited use of engaging learning media suitable for young learners. Therefore, this study aimed to improve children’s ability to recognize Hijaiyyah letters through the use of flashcard media designed to be visually appealing and easy for children to understand. This research employed classroom action research using the Kemmis and McTaggart model, conducted in two cycles. The subjects consisted of 13 children in group B3, comprising 7 boys and 6 girls, with one classroom teacher involved as a collaborator. The findings showed a significant improvement in children’s recognition abilities. In the initial condition, only 15.38% of the children were in the “developing as expected” category. After the implementation of flashcards in cycle I, the percentage increased to 53.85%. Further improvement occurred in cycle II, where 23.08% reached the same category and 76.92% achieved the “very well developed” category. These results indicate that flashcard media is effective in enhancing young children’s ability to recognize Hijaiyyah letters.